Downregulation of hnRNPA1 inhibits hepatocellular carcinoma cell progression by modulating alternative splicing of ZNF207 exon 9 - Ouyang, Qi; He, Wenhui; Guo, Yiping; Li, Lin; Mao, Ying; Li, Xiang; Xiang, Shuanglin; Hu, Xiang; He, Jun (Frontiers in Oncology, 2025)
IntroductionHepatocellular carcinoma (HCC) is the most prevalent liver cancer and a leading cause of cancer-related deaths worldwide. Heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) plays a critical role in RNA metabolism, including alternative splicing, which is linked to cancer progression. Our study investigated the role of hnRNPA1 in HCC and its potential as a therapeutic target.MethodsWe analyzed hnRNPA1 expression in HCC tissues compared to non-tumor tissues using RNA-seq and immunohistochemistry. hnRNPA1 was knocked down in Hep G2 cells to assess its impact on cell proliferation, migration, and apoptosis using scratch assays, flow cytometry, qPCR, and Western blot. We also explored the interaction between hnRNPA1 and ZNF207, as well as its splicing effects and downstream signaling pathways by RIP assay, bioinformatics, qPCR and Western blot.ResultshnRNPA1 was significantly upregulated in HCC tissues compared to normal tissues, correlating with poor patient survival. hnRNPA1 knockdown reduced Hep G2 cell proliferation and migration while increasing apoptosis. We identified that hnRNPA1 bound to ZNF207 and regulated its exon 9 skipping, influencing ZNF207 splicing and the PI3K/Akt/mTOR pathway, key regulators of cell growth and survival.ConclusionOur findings demonstrate that hnRNPA1 promotes HCC progression by regulating ZNF207 splicing and the PI3K/Akt/mTOR pathway. hnRNPA1-ZNF207 interaction represents a potential therapeutic target for HCC, providing insights into the molecular mechanisms underlying HCC progression.